2022
DOI: 10.3390/su142013414
|View full text |Cite
|
Sign up to set email alerts
|

The Influence and Mechanism of Digital Economy on the Development of the Tourism Service Trade—Analysis of the Mediating Effect of Carbon Emissions under the Background of COP26

Abstract: This study explores the impact and mechanism of the digital economy on the tourism service trade. We adopted two-way fixed effects and mediating effects models, and conducted empirical studies based on panel data of 30 provinces (municipalities and autonomous regions) in China. The results show that the digital economy can significantly improve the development of the tourism service trade, and has a certain role in carbon emission reduction. This conclusion remains valid after a series of robustness tests and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 48 publications
1
13
0
Order By: Relevance
“…The digital economy has become an economy of new business models and new markets [1]. In some studies, the digital economy has been linked to various issues, such as labor [2][3][4][5][6], carbon emissions [7][8][9][10][11], population aging [12,13], artificial intelligence [14,15], foreign trade [16][17][18], and rural revitalization [19,20]. Under the continuous influence of Corona Virus Disease 2019, there are uncertainties in the global economic recovery.…”
Section: Introductionmentioning
confidence: 99%
“…The digital economy has become an economy of new business models and new markets [1]. In some studies, the digital economy has been linked to various issues, such as labor [2][3][4][5][6], carbon emissions [7][8][9][10][11], population aging [12,13], artificial intelligence [14,15], foreign trade [16][17][18], and rural revitalization [19,20]. Under the continuous influence of Corona Virus Disease 2019, there are uncertainties in the global economic recovery.…”
Section: Introductionmentioning
confidence: 99%
“…A study from China showed that the development of the digital economy promotes the integration of the culture with the tourism industry in China during the pandemic (Li et al, 2022). The development of the digital economy in each country (region) can propel the development of the tourism industry by improving the quality of institutions, strengthening the capacity of market regulation, increasing trade freedom (Kumar and Kumar, 2020;Tang, 2023), and achieving the improvement of tourism industry performance through technological leaps in distribution channels (Berné et al, 2015;Zhang and Shang, 2022). Third, research about the feedback effect of the development of the tourism industry on the implementation of the degree of informatization and information technology innovation.…”
Section: Tourism Industry Development and Informatizationmentioning
confidence: 99%
“…As a result, the types of tourism products and business models can be greatly enriched (He et al, 2018;Hameed et al, 2022) and technological innovation in the tourism industry can be progressed to enhance the development of the tourism industry (Jadhav and Mundhe, 2011). Second, informatization improves the marketing management and distribution capabilities of the tourism industry (Berné et al, 2015;Zhang and Shang, 2022). The Internet, as one of the most essential marketing tools in modern times, realizes direct contact between the supply side and tourists.…”
Section: Mechanism Analysis and Theoretical Frameworkmentioning
confidence: 99%
“…Due to the lockdowns and the economic downturns because of the COVID-19 pandemic, millions of individuals have lost their jobs. Many industries, such as tourism, have been hit hard, and many scholars have begun to study the role of high and new technologies, such as digital technology, in revitalizing the national economy (Zhang and Shang, 2022). Many countries throughout the world are undergoing similar transformations.…”
Section: Literature Reviewmentioning
confidence: 99%